RAS mutation prevalence among patients with metastatic colorectal cancer: a meta-analysis of real-world data - Kafatos, George; Niepel, Daniela; Lowe, Kimberley; Jenkins-Anderson, Sophie; Westhead, Hal; Garawin, Tamer; Traugottová, Zuzana; Bilalis, Antonios; Molnar, Edit; Timar, Jozsef; Toth, Erika; Gouvas, Nikolaos; et al. (Biomarkers in medicine, 2017)
AIM: A confirmed wild-type RAS tumor status is commonly required for prescribing anti-EGFR treatment for metastatic colorectal cancer. This noninterventional, observational research project estimated RAS mutation prevalence from real-world sources. MATERIALS & METHODS: Aggregate RAS mutation data were collected from 12 sources in three regions. Each source was analyzed separately; pooled prevalence estimates were then derived from meta-analyses. RESULTS: The pooled RAS mutation prevalence from 4431 tumor samples tested for RAS mutation status was estimated to be 43.6% (95% CI: 38.8-48.5%); ranging from 33.7% (95% CI: 28.4-39.3%) to 54.1% (95% CI: 51.7-56.5%) between sources. CONCLUSION: The RAS mutation prevalence estimates varied among sources. The reasons for this are not clear and highlight the need for further research.
Keywords: exony; Prevalence; Exons; protoonkogenní proteiny B-raf; protoonkogenní proteiny p21(ras); Colorectal Neoplasms; Proto-Oncogene Proteins B-raf; Proto-Oncogene Proteins p21(ras); prevalence; Mutation; kolorektální nádory; mutace; lidé; Survival Rate; Biomarkers, Tumor; Humans; nádorové biomarkery; míra přežití